2009
DOI: 10.4037/ajcc2009621
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health, Ventilator-Associated Pneumonia, and Intracranial Pressure in Intubated Patients in a Neuroscience Intensive Care Unit

Abstract: Background Although oral health affects systemic health, studies of oral health during intubation among critically ill neuroscience patients are lacking. Furthermore, the effect of oral care on intracranial pressure among critically ill patients in a neuroscience intensive care unit is unknown. Objectives To describe changes in oral health and development of ventilatorassociated pneumonia during intubation among patients in a neuroscience intensive care unit and to assess the influence of oral care on intracra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
1
16

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(88 citation statements)
references
References 37 publications
2
69
1
16
Order By: Relevance
“…So, it can be said that oral care with use of chlorhexidine solution formula was the best solution that improve oral health status. This finding supported by Prendergast et al, (2009) (35) who found that during intubation, total oral assessment grade scores increased from baseline to 12 th day. Regarding to modified clinical pulmonary infection sheet score (CPIS), the current study for body temperature, observed that there was no significant difference observed among patients in study and control groups on the first, second, third, fourth and fifth day.…”
Section: Effects Of Chlorhexidine Solution Formula On Oral Health Stasupporting
confidence: 81%
“…So, it can be said that oral care with use of chlorhexidine solution formula was the best solution that improve oral health status. This finding supported by Prendergast et al, (2009) (35) who found that during intubation, total oral assessment grade scores increased from baseline to 12 th day. Regarding to modified clinical pulmonary infection sheet score (CPIS), the current study for body temperature, observed that there was no significant difference observed among patients in study and control groups on the first, second, third, fourth and fifth day.…”
Section: Effects Of Chlorhexidine Solution Formula On Oral Health Stasupporting
confidence: 81%
“…[8][9][10][11][12][13][14][15][16][17] In contrast, administration of oral care by using either manual or electric toothbrushes among intubated neurologically impaired patients does not result in significant increases in ICP. 18,19 Similarly, Olson et al, in a series of 3 articles, 5,20,21 explored the effects of chest percussion therapy on ICP, finding that such therapy does not adversely affect ICP and may be associated with lower ICP for some patients. Although these interventions are often necessary to provide adequate care for critically ill patients, as they reduce risk of ventilatorassociated pneumonia and pressure ulcers, other nursing interventions are performed with the aim of specifically decreasing ICP values.…”
Section: Review Of Literaturementioning
confidence: 99%
“…alteração bioquímica da superfície bucal do paciente, aumentando a adesão e consequentemente sua colonização por patógenos respiratórios 14,15 . Um estudo realizado por Oliveira et al 16 descreve uma amostra de 30 pacientes em que foram encontrados 70% de patógenos respiratórios no biofilme dental, 63,33% no dorso da língua e 73,33% no filtro do respirador artificial, corroborando com a literatura sobre tudo na necessidade de uma maior investigação que aponte o perfil microbiológico da cavidade bucal dos pacientes admitidos no CTI, em decorrência de uma incidência significativa de suporte ventilatório através de intubação orotraqueal e traqueostomia em 84% (n=31) e de um expressivo número de pacientes com comprometimento na integridade da cavidade bucal.…”
Section: Arch Health Invest 6(7) 2017unclassified